2023
DOI: 10.1002/adsr.202200086
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Halloysite‐Modified Chitosan/Polyvinylpyrrolidone Nanofibers for Ultrasensitive Self‐Powered Motion Monitoring

Abstract: High flexibility, porosity, and antibacterial activity are extremely desired for wearable health monitoring, which is beneficial to simultaneously promote wearing comfort and safety. In this study, an antibacterial nanofibers‐based triboelectric generator (AN‐TENG) composed of the flexible chitosan/polyvinylpyrrolidone modified with halloysite nanotubes (CTS/PVP/HNTs) nanofibers and cube‐arrays structured Ecoflex film is proposed for simultaneously energy harvesting and self‐powered human motion monitoring. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…[45] Aiming at the above problems, the triboelectric nanogenerator (TENG) is an emerging new energy harvesting technology that can efficiently convert wind, raindrop and wave energies with low frequency (1−5 Hz) into electric energy. [46] Integrating PDRC film into the design of TENG is an emerging new research hotspot since it is an efficient way to simultaneously achieve energy saving and energy generation. [47,48] Considering the practical application requirements, the solar reflectance and the triboelectric property of the PDRC film should be further enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…[45] Aiming at the above problems, the triboelectric nanogenerator (TENG) is an emerging new energy harvesting technology that can efficiently convert wind, raindrop and wave energies with low frequency (1−5 Hz) into electric energy. [46] Integrating PDRC film into the design of TENG is an emerging new research hotspot since it is an efficient way to simultaneously achieve energy saving and energy generation. [47,48] Considering the practical application requirements, the solar reflectance and the triboelectric property of the PDRC film should be further enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…PLA, which contains two asymmetric carbon atoms, is commonly used as a positive friction layer due to its high degree of polarization upon triboelectrification and positron affinity in the triboelectric series. Mohapatra et al fabricated a positive friction layer by adding carbon nanotube-ZnO core–shell nanoparticles into PLA, which could improve the charge generation ability and TENG output voltage. It has been reported that CS is also a good candidate to prepare the positive friction layer of TENG since its protonated amino group realizes a strong electron donor capacity. TPU is a high-elasticity material with abrasion resistance and low-temperature flexibility, which is mostly used as the base or packaging material of sensors. , In addition, TPU with strong electronegativity has been developed for the friction layer of TENGs . For example, Shi et al constructed a single-electrode TENG composed of a TPU layer, silver nanowire layer, and poly (vinyl alcohol)/chitosan (PVA/CS) composite by ES and spraying alternately.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] By autonomously converting mechanical stimuli into electric signals, TENGs have been widely employed to realize self-powered tactile sensing, motion recognition, human-machine interfacing, and disease diagnosis. [32,33] Integrating PDRC technology to the versatile design of TENG is expected to simultaneously achieve efficient utilization of sustainable energies, energy conservation, and emission reduction, which is conductive to optimize the world's energy consumption structure and promote the realization of carbon neutrality. The main challenges lie in the ingenious structure design and material optimization to guarantee the performance of such a versatile energy saving and energy generation system, in which the candidate materials should concurrently maintain the PDRC function and the energy harvesting efficiency.…”
Section: Introductionmentioning
confidence: 99%